Stress and its associated factors in mothers with preterm infants in a private tertiary care hospital of Karachi, Pakistan: an analytical cross-sectional study - Yasmin Parpio; Salima Akbar; Afshan Akber (BMJ Open)
Objectives This goal of this research is to present a comprehensive method for evaluating stress and the factors that contribute to it in mothers of premature babies.Design Analytical cross-sectional study.Setting Data were collected from inpatient service for preterm infants including neonatal intensive care unit, and neonatal step-down units of the Aga Khan University Hospital—a private tertiary care hospital in Karachi, Pakistan.Participants Mothers aged 18 years and above who delivered preterm infants (gestational age of preterm below 37 weeks) in a private tertiary care hospital in Karachi, Pakistan.Primary outcome Stress in mothers of preterm infants.Results 200 participants with a mean age of 30.12 years (SD ±5.21) were assessed. The level of stress identified using the perceived stress scale (PSS) among mothers who had delivered preterm infants was significantly higher as compared with other countries around the world. Based on the criteria of PSS scoring, the majority of the participants (92%, n=184) were categorised as having high perceived stress and 8% (n=16) of the mothers fell into the category of moderate stress.Conclusions The study findings suggest high levels of perceived stress among mothers of preterm infants. The factors associated with the stress among mothers of preterm infants included immunisation of newborn, education and occupation status of mothers, substance abuse by mother, gender preference from family, planning for further children, consumption of balance diet, education status of husband, mode of socialisation, years of marriage and hours of sleep.